The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1088/0963-0252/12/4/316
|View full text |Cite
|
Sign up to set email alerts
|

High quality diamond formation by electron temperature control in methane–hydrogen plasma

Abstract: We report a new method for the nucleation and growth of diamonds by employing an electron-temperature control technique in CH 4 /H 2 radio frequency glow discharge plasma under a low gas pressure of 100 mTorr. The electron temperature in the plasma is controlled under constant gas pressure in a range from 0.5 to 2.5 eV continuously by changing the open area of the slits situated around a grid that is kept at the floating potential. It is observed that the film quality is changed in accordance with the variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…In the particle-levitation region they lose their kinetic energy through ionizations and collisions with molecules. In the particle-levitation region there is no rf electric field to accelerate electrons, therefore, we have a low electron-temperature plasma in this region [5,6]. This procedure to control the electron temperature was investigated in detail by Shimizu and coworkers [5,6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the particle-levitation region they lose their kinetic energy through ionizations and collisions with molecules. In the particle-levitation region there is no rf electric field to accelerate electrons, therefore, we have a low electron-temperature plasma in this region [5,6]. This procedure to control the electron temperature was investigated in detail by Shimizu and coworkers [5,6].…”
Section: Methodsmentioning
confidence: 99%
“…For controlling the electron temperature, K. Kato et al developed a grid method [5]. Furthermore, it has been found that the electron temperature plays an important role for diamond deposition [6] and a-Si:H process [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, we have already demonstrated that the grid bias method can still control e over a wide range [9]. In fact, high-quality diamond was produced in RF discharge CH 4 /H 2 plasmas [14], where e was decreased by varying mechaniclly the length of slits in plasmas [8]. In the case of Argon plasma, e was widely controlled by almost one order of magnitude by changing the mesh size of the grid electrode.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the growth of diamond on Mo was relatively easy because of a formation of Mo 2 C layer, which could provide a favorable intermediate layer for diamond nucleation. The growth of diamond on Ni substrate was also studied [2,7] Here, high quality diamond could be produced in a low electron temperature plasma, where a novel method for the control of electron energy distribution function has been developed in order to reduce higher order dissociation of CH 4 [8]. This technique was applied to CH 4 / H 2 plasma for diamond deposition.…”
Section: Introductionmentioning
confidence: 99%